Influential predictors of students' academic achievement in online peer learning among undergraduate students - Mohammed, Ibrahim; Che Hassan, Norlizah; Ab. Jalil, Habibah (International Institute for Science, Technology & Education, 2015)
Social media is widely used by students. Previous studies have projected conflicting results regarding the influence of online peer learning via social media on academic achievement. The purpose of this study is to identify the factors that impact on academic achievement. Building on the literature, the study proposed a conceptual model consists of self-efficacy; engagement, performance expectancy, social influence, peer feedback, and collaboration were incorporated as independent variables that influence the academic achievement. Data was collected from 369 undergraduate students. The findings of regression analysis showed that the strongest predictor of academic achievement in online peer learning was performance expectancy followed by collaboration, social influence, and engagement. An online peer learning influences significantly on academic achievement. Decision makers were advised to support the implementation of online peer learning in universities.